2016
DOI: 10.1186/s12862-016-0705-1
|View full text |Cite
|
Sign up to set email alerts
|

Extremophile Poeciliidae: multivariate insights into the complexity of speciation along replicated ecological gradients

Abstract: BackgroundReplicate population pairs that diverge in response to similar selective regimes allow for an investigation of (a) whether phenotypic traits diverge in a similar and predictable fashion, (b) whether there is gradual variation in phenotypic divergence reflecting variation in the strength of natural selection among populations, (c) whether the extent of this divergence is correlated between multiple character suites (i.e., concerted evolution), and (d) whether gradual variation in phenotypic divergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 77 publications
3
54
0
Order By: Relevance
“…The clearly defined selective regimes in extreme environments enable hypothesis‐driven tests of responses at all levels of biological organization and facilitate integrative approaches to study the causes and consequences of adaptive evolution (Nevo, ; Tobler, Riesch, & Plath, ). In addition, the availability of replicated lineages exposed to the same physicochemical stressors allows for evolutionary analyses in a comparative context, spanning vast geographic and phylogenetic distances (Riesch, Plath, Schlupp, Tobler, & Langerhans, ; Riesch et al., ). Here, we review recent research on fishes inhabiting hydrogen sulphide‐rich springs that sheds light onto mechanisms of adaptation, speciation and convergent evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The clearly defined selective regimes in extreme environments enable hypothesis‐driven tests of responses at all levels of biological organization and facilitate integrative approaches to study the causes and consequences of adaptive evolution (Nevo, ; Tobler, Riesch, & Plath, ). In addition, the availability of replicated lineages exposed to the same physicochemical stressors allows for evolutionary analyses in a comparative context, spanning vast geographic and phylogenetic distances (Riesch, Plath, Schlupp, Tobler, & Langerhans, ; Riesch et al., ). Here, we review recent research on fishes inhabiting hydrogen sulphide‐rich springs that sheds light onto mechanisms of adaptation, speciation and convergent evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding complex phenotypic divergence is critical for comprehending adaptive evolution. Yet few studies have explicitly investigated joint/independent changes of disparate type of phenotypes (Conner and Via 1993, Hendry and Quinn 1997, Wesner et al 2011, Riesch et al 2016. Here, our PLS-SEM results showed that the two character suites did not greatly influence one another during phenotypic divergence among blue holes.…”
Section: How Do Life Histories and Morphology Co-vary And Diverge Indmentioning
confidence: 63%
“…the guppy Poecilia reticulata: Reznick and Endler 1982 (life history); Hendry et al 2006 (morphology)). In the comparatively rare cases where co-divergence in multiple trait suites are examined (Conner and Via 1993, Hendry and Quinn 1997, Wesner et al 2011, Riesch et al 2016, seldom is this combined with the study of multiple selective factors. However, only by simultaneously investigating multiple types of traits and multiple agents of selection can we more fully understand the complexity of adaptive diversification (Lardner 2000, DeWitt andLangerhans 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, display rates are lower because males trade off sexual selection (opportunity to reproduce) with natural selection (due to predation; Godin, 1995;Langerhans et al, 2005;Luyten & Liley, 1985), and competition among males occurs after fertilization in the form of sperm competition rather than prior to copulation (Kawase et al, 2017;Stockley et al, 1997). Though studies have described testes mass as it fluctuates in various high-mortality environments (Riesch et al, 2011), few studies have yet revealed how testes mass correlates with body mass among size classes and predation environments (Riesch et al, 2013(Riesch et al, , 2016.…”
Section: Gambusia Hubbsi Males Have Higher Gonadosomatic Indexes (Gsimentioning
confidence: 99%
“…In contrast, Poecilia mexicana males living in high‐mortality sulphidic environments have lower GSIs than those living in low‐mortality nonsulphidic environments (Riesch, Plath, & Schlupp, ). More recently, Poecilia mexicana and other related species exhibited no substantial differences in GSI across environments differing in mortality rates (Riesch et al, ). The results in Gambusia hubbsi (Riesch et al, ) are what we would expect according to life history theory: In high‐predation environments, males have less competition (lower density of conspecifics) prior to fertilization than males in low‐predation environments.…”
Section: Introductionmentioning
confidence: 99%